Розробка методик визначення антиоксидантної активності препаратів на основі лікарських рослин - Lipkovska, N. O.; Barvinchenko, V. M.; Turov, V. V.; Kartel, M. T. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2014)
The method of spectrophotometric determination of total content of natural polyphenol antioxidants using tetrabenzo-[b,f,j,n][1,5,9,13]-tetraazacyclohexadecine - Cu(II) complex was developed and optimized. Caffeic acid and quercetin were proposed as standard substances. This method was approved in the analysis of the dietary supplement balzasil. Based on test results it was shown the perspectivity of quality control and standardization of herbal drugs by their pharmacologically important characteristic – antioxidant activity.